1997
DOI: 10.1164/ajrccm.156.4.9603061
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Proteins-A and -B Are Elevated in Plasma of Patients with Acute Respiratory Failure

Abstract: Surfactant protein-A (SP-A) leaks into the circulation of patients with acute respiratory distress syndrome (ARDS) or acute cardiogenic pulmonary edema (APE) in a manner inversely related to lung function. Since surfactant protein-B (SP-B) is synthesized as a precursor considerably smaller than alveolar SP-A, we investigated whether it enters the circulation more readily. Reactivities consistent with SP-B proprotein (approximately 42 to approximately 45 kD) and the approximately 25 kD processing intermediate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
99
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 35 publications
(76 reference statements)
18
99
2
4
Order By: Relevance
“…In our study we found increase levels of SP-D in patients with smoker COPD and non-smoker COPD this might be due to deleterious effects oxidants from tobacco smoke and oxidants originated from endogenous sources on lung tissue cause release of SP-D in blood stream. The increased level of SP-D in the blood stream depends on the extent of injury to the lung tissue and is directly related to pulmonary function [25][26][27]. In our study we obtain inverse correlation between SP-D with FEV1% predicted and FEV1/FVC % ratio in COPD patients.…”
Section: Discussionsupporting
confidence: 60%
“…In our study we found increase levels of SP-D in patients with smoker COPD and non-smoker COPD this might be due to deleterious effects oxidants from tobacco smoke and oxidants originated from endogenous sources on lung tissue cause release of SP-D in blood stream. The increased level of SP-D in the blood stream depends on the extent of injury to the lung tissue and is directly related to pulmonary function [25][26][27]. In our study we obtain inverse correlation between SP-D with FEV1% predicted and FEV1/FVC % ratio in COPD patients.…”
Section: Discussionsupporting
confidence: 60%
“…Many of these proteins were also abundant in plasma and were presumably plasma-derived, as has been previously suggested (51,52). The flow of proteins across the alveolar-capillary wall is bidirectional in normal lungs: plasma proteins enter the alveoli down a steep pressure gradient, while lung-specific surfactant proteins, present in high concentrations on the alveolar epithelial lining surface, normally diffuse across the capillary wall down their own steep concentration gradients and can be detected in blood (53,54). Under conditions of pulmonary artery hypertension, the in-flow of plasma proteins across the capillary wall would likely be increased while the rate of absorption of surfactant into the blood or lymph would be reduced.…”
Section: Discussionmentioning
confidence: 67%
“…Another pneumoprotein is surfactant-associated protein A (SP-A), a ~28-35 kDa protein mainly secreted by alveolar type II cells, occurring in the respiratory tract and serum in monomeric and various oligomeric forms [14,15]. Similar findings have been made with the ~18 kDa surfactantassociated protein B (SP-B), secreted by both alveolar and bronchiolar cells [16].…”
mentioning
confidence: 66%